2019
DOI: 10.1530/ec-19-0260
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor expression in parathyroid neoplasms

Abstract: Introduction Parathyroid carcinoma represents a rare cause of primary hyperparathyroidism. Distinguishing carcinoma from the benign tumors underlying primary hyperparathyroidism remains challenging. The diagnostic criteria for parathyroid carcinoma are local and/or metastatic spreading. Atypical parathyroid adenomas share other histological features with carcinomas but lack invasive growth. Somatostatin receptors are commonly expressed in different neuroendocrine tumors, but whether this also holds for parathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Similar to other neuroendocrine tumors, parathyroid cancers have also been found to express somatostatin receptors (SSTs). Immunohistochemical studies have shown a prevalence of SST 1–5 within either the cytoplasm or nucleus of parathyroid tumors [68]. The extent of SST 2–5 profile expression is variable, depending on how benign or malignant the tumor is.…”
Section: Adjuvant Therapy For Parathyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other neuroendocrine tumors, parathyroid cancers have also been found to express somatostatin receptors (SSTs). Immunohistochemical studies have shown a prevalence of SST 1–5 within either the cytoplasm or nucleus of parathyroid tumors [68]. The extent of SST 2–5 profile expression is variable, depending on how benign or malignant the tumor is.…”
Section: Adjuvant Therapy For Parathyroid Cancermentioning
confidence: 99%
“…At this time, SST 5 offers us another potential new marker for parathyroid cancer. Similar to the fact that peptide receptor radiotherapy is being utilized in cases of pancreatic neuroendocrine tumors, there may possibly be a role for its utilization in parathyroid carcinoma, although published studies on the same are pending at this time [68].…”
Section: Adjuvant Therapy For Parathyroid Cancermentioning
confidence: 99%
“…MIBI scintigraphy reveals uptake of PHPT, thus is useful for localization of ectopic diseases and distant matastasis [ 1 ]. Also, since a parathyroid carcinoma expresses somatostatin receptors, scintigraphy may be beneficial for showing that expression and distant metastasis related to the tumor [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that normal parathyroid cells express SSTRs ( 8 ). In a recent study, Storvall et al also reported that parathyroid adenomas, atypical adenomas, and carcinomas all express SSTR subtypes 1-5 and suggested that SSTR5 may serve as a potential biomarker for malignancy ( 9 ). Furthermore, long-acting octreotide has been reported as a possible alternative treatment for PHPT due to adenomas in patients with multiple endocrine neoplasia type 1 (MEN1) ( 5 ).…”
Section: Discussionmentioning
confidence: 99%